2020
DOI: 10.1021/acsami.0c10487
|View full text |Cite
|
Sign up to set email alerts
|

Zn–Al Layered Double Hydroxide Film Functionalized by a Luminescent Octahedral Molybdenum Cluster: Ultraviolet–Visible Photoconductivity Response

Abstract: A c c e p t e d M a n u s c r i p t the industry. During the last few decades, the use of various wide band-gap semiconducting inorganic materials, such as ZnO, MoS2, ZnS, SiC for the light energy converters, has been mainly reported due to their simple structure and high photoconductive gain. [1][2][3][4] The visible (Vis) sensing photodetector using solar light energy became an interesting study for sustainable energy development goals. 5, However, the development of broadband photodetectors, having an effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…Ligated Mo 6 -cluster-containing compounds used for sensing activity are currently limited to oxygen sensor [ 67 , 68 ], pH sensing [ 69 ], biological sensing [ 70 ], and photo-response [ 58 , 71 ]. According to theoretical calculations, such compounds are predicted to have a good selectivity for NH 3 in the NRR [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligated Mo 6 -cluster-containing compounds used for sensing activity are currently limited to oxygen sensor [ 67 , 68 ], pH sensing [ 69 ], biological sensing [ 70 ], and photo-response [ 58 , 71 ]. According to theoretical calculations, such compounds are predicted to have a good selectivity for NH 3 in the NRR [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to theoretical calculations, such compounds are predicted to have a good selectivity for NH 3 in the NRR [ 29 ]. Previous studies have also demonstrated that they exhibit a photo-response and can react with NH 3 to form Mo x N y species at 400 °C [ 46 , 58 , 71 ]. Thus, we inferred that Mo 6 cluster iodides should have a specific adsorption of NH 3 even at room temperature and that this adsorption could cause a potential change when a voltage is applied to the MI@FTO, which was proved to be an ambipolar material ( E g = 1.9 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The ever-increasing energy demand has posed a serious threat to existing resources, especially fossil fuels. An urgent need has emerged for the development of novel materials with multifunctional characteristics. In this row, layered double hydroxides (LDHs), composed of multimetal clay materials, have emerged as potential candidates created by brucite layers involving metal cations surrounded by hydroxyl anions octahedrally to stabilize M 2+ (OH) 6 /M 3+ / 4+ (OH) 6 octahedra. , Multivalent cations in the structure make them ultraefficient in redox reactions, which indeed prove their suitability as electrode materials for energy-related applications. Alongside, facile stabilization, at lower temperatures, with intriguing hierarchical and freestanding morphologies on conductive substrates makes them even more interesting. Their capability to hold multiple cations in the single structure improves the charge transfer kinetics. Moreover, the easy tunability of cationic cores by doping/de-doping of multiple similarly sized/charged cations in the host layers and exchangeability of anions without altering the structure bestows them with excellent electrochemical properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Layered double hydroxides (LDHs) are a class of inorganic layered materials that have received great attention due mainly to their anion exchange properties, which make them promising in such diverse fields as catalysis, corrosion inhibition, environmental remediation, UV–vis photodetection, and drug delivery. , These hydrotalcite-type materials have the general formula [M 1– x 2+ M x 3+ (OH) 2 ] x + ( A m – ) x / m · n H 2 O, where M 2+ and M 3+ are divalent and trivalent cations, respectively, and A m – is an interlayer anion with charge − m . The structure is derived from that of brucite [Mg­(OH) 2 ] by isomorphous replacement of some of the divalent cations by trivalent ones to give positively charged layers that require the presence of charge-balancing interlayer anions .…”
Section: Introductionmentioning
confidence: 99%